Analisis Prinsip Kesantunan Berbahasa dalam Acara Mata Njawa di Stasiun Televisi Trans 7 - Septiarni, Intan; Alber, Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The principle of politeness in language is an effort to avoid conflict between the speaker and the interlocutor in the communication process. Language politeness is an utterance that uses words, intonations, and sentences that do not harm the interlocutor. The problem in this research is how are the principles of language politeness in the Mata Najwa program on Trans 7 Television Station?. The purpose of this study is to describe, analyze, and interpret the principles of language politeness in the Mata Najwa program at Trans 7 Televisa Station. The theory that the author uses is the theory of politeness principles Rahardi (2005). The source of this data is all the speeches of the presenters and guest stars in the Mata Najwa program on the theme of the End of the Year Guyub at Trans 7 Televisa Station. The method used is descriptive method. The technique that the writer uses in this research is the documentation technique, the listening technique, and the note-taking technique. The results showed that there were 593 utterances in the Mata Najwa program on the Trans 7 Television Station. The results of the author's research regarding the principle of politeness which consists of 6 maxims, namely 1) the maxim of wisdom that obeys is 20 utterances and the maxim of wisdom that violates is 5 utterances, 2) the maxim of generosity that obeys is 5 utterances and the maxim of generosity that violates is 2 utterances, 3 ) the maxim of respect that obeys totaling 23 utterances and the violating maxims of appreciation amounted to 5 utterances, 4) the maxim of obeying were 16 utterances and the maxim of simplicity that violated the utterances of 10, 5) the maxims of agreement which obeyed were 10 utterances and the maxim of agreement that violated the utterances were 4 utterances, 6) The sympathetic maxim that obeys is 3 utterances and the sympathetic maxim that violates is 4 utterances.